Occurrence and the first molecular genotyping of Dibothriocephalus dendriticus and Dibothriocephalus ditremus (Cestoda: Diphyllobothriidea) in salmonids from Iceland - Ivica Králová-Hromadová; Eva Čisovská Bazsalovicsová; Alžbeta Radačovská; Lucia Dinisová; Karl Skírnisson (Current Research in Parasitology and Vector-Borne Diseases)
The occurrence of Dibothriocephalus dendriticus and Dibothriocephalus ditremus (Cestoda: Diphyllobothriidea) in salmonids from lakes Hafravatn, Thingvallavatn, Másvatn, and Ytra-Hólavatn in Iceland was studied. The exact taxonomic identification of plerocercoids was performed by a recently validated molecular discriminatory PCR-based approach using D. dendriticus-specific Dd_8 primers. Of 1684 plerocercoids isolated from 58 fish (40 Arctic charrs Salvelinus alpinus, and 18 brown trout Salmo trutta), 318 (18.9%) larvae were identified as D. dendriticus and 1366 (81.1%) as D. ditremus. The prevalence of D. ditremus was high at all four localities, ranging from 54.2% to 100%. Similarly, the prevalence of D. dendriticus ranged from 50.0% to 100% in all lakes, except for Ytra-Hólavatn, where a prevalence of 14.3% was recorded. All examined specimens of large benthivorous (LB) charr from Thingvallavatn were negative, which was related to the specific habitat and the different feeding specialization of the LB morph. In contrast, the prevalence and the intensity of infection with both D. dendriticus and D. ditremus were high in piscivorous and planktivorous Arctic charr morphs. The intensity of infection with D. dendriticus was lower in all four lakes compared to much higher values detected for D. ditremus. The relative abundance of D. dendriticus and D. ditremus plerocercoids in individual fish hosts showed substantially lower values for D. dendriticus in all four lakes. This can be explained by various climatic conditions required for egg development and by the different feeding ecology of aquatic birds, definitive hosts of both tapeworms.